Inoculation with Azospirillum brasilense for the production of maize for silage (Research, Society and Development, 2022)
Nitrogen fertilization plays a fundamental role in determining the productivity and profitability of the corn crop. Azospirillum genus has the ability, when associated with grasses, to fix atmospheric nitrogen, assist in the solubilization of inorganic phosphate and provide growth regulators that contribute to plant growth. This work aimed to evaluate the effect of using inoculation with Azospirillum brasilense on corn seeds grown for silage production in Santana do Livramento, RS. The treatments consisted of comparing corn plants for the production of silage with and without inoculation in the sowing of the strains AbV5 and AbV6 of Azospirillum brasilense, in the concentration of 2x108 CFU ml-1. The parameters of plant height, stem diameter, mass of the aerial part of the plant, mass of the root, average mass of the ear, quantity of ears produced per plant and productivity were analyzed from 20 replicates per treatment. The contents of starch, protein, crude fiber, mineral matter, moisture and volatiles, ADF, NDF and dry matter of corn silage were also obtained from three replicates per treatment. The experiment was conducted in a completely randomized design. The results were submitted to the Tukey test, at the level of 5% probability of error. The use of inoculant provided higher plant height and reduced root mass and starch and silage protein contents. The other parameters analyzed were not altered by inoculating the seeds with A. brasilense.